2017
DOI: 10.1016/j.scs.2017.09.021
|View full text |Cite
|
Sign up to set email alerts
|

A methodology to determine the potential of urban densification through roof stacking

Abstract: HIGHLIGHTS Seven approaches present solutions for urban densification  Successful roof stacking requires integrating urban, engineering and architectural aspects  European cities have a great potential to be densified through roof stacking  30% of the population increase could be covered by roof stacking in Brussels ABSTRACTFacing the need to accommodate a growing number of inhabitants in major European cities, this research aimed to establish a methodology that facilitates decision making on urban densifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 31 publications
0
36
0
2
Order By: Relevance
“…Those values are considered in the replacementRC, and operational costsOC [16], represented by the following Eqs. (6) and 7.…”
Section: Life Cycle Costing (Lcc)mentioning
confidence: 99%
See 3 more Smart Citations
“…Those values are considered in the replacementRC, and operational costsOC [16], represented by the following Eqs. (6) and 7.…”
Section: Life Cycle Costing (Lcc)mentioning
confidence: 99%
“…Although the scientific community has proposed a numerous of multi-objective optimization methods, there are a limited number of studies that consider the implications of roof stacking on the reduction of carbon emissions and energy use of existing buildings [6][7][8][32][33][34][35][36]. Generally, it is argued that by providing more compact cities, it is possible to reduce the energy use on the building and transportation scale [37][38][39].…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though roof stacking is increasingly taking place worldwide with high potential in major European cities [33,34], very few literature was found that studied this phenomenon. There have been a couple of attempts to classify roof stacking in terms of approach, shape or structural capacity.…”
Section: Research On Roof Stackingmentioning
confidence: 99%